2012
DOI: 10.1039/c2cp41115f
|View full text |Cite
|
Sign up to set email alerts
|

Properties of water in the interfacial region of a polyelectrolyte bilayer adsorbed onto a substrate studied by computer simulations

Abstract: We study the static and dynamic properties of water near a poly(styrene sulfonate)/poly(diallyldimethylammonium) (PSS/PDADMA) bilayer adsorbed onto a substrate by atomistic molecular dynamics simulations. Qualitative changes in the dynamics of water in the proximity of the adsorbed bilayer are observed - such as in the lateral diffusion, residence time and hydrogen-bonding lifetime - as compared with water in the presence of the bare substrate. Static properties of water are similarly influenced, and a high po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Understanding water solvation of various self-assembled aggregates is necessary for predicting and perhaps manipulating a number of macroscopic substrate properties. 11 Among experiments used to assess the properties of interfaces, vibrational sum frequency generation (VSFG) is widely used to study the orientation of water at interfaces, [12][13][14] while adsorption [15][16] and scattering experiments [17][18][19][20] are performed to determine the structure of adsorbed surfactant layers. Surfactants can aggregate on a surface, causing a decrease in the density of interfacial water because of excluded-volume effects.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding water solvation of various self-assembled aggregates is necessary for predicting and perhaps manipulating a number of macroscopic substrate properties. 11 Among experiments used to assess the properties of interfaces, vibrational sum frequency generation (VSFG) is widely used to study the orientation of water at interfaces, [12][13][14] while adsorption [15][16] and scattering experiments [17][18][19][20] are performed to determine the structure of adsorbed surfactant layers. Surfactants can aggregate on a surface, causing a decrease in the density of interfacial water because of excluded-volume effects.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the results of a recent computational study on the mesoscopic dynamics of electro-osmotic flows with charged walls 30 and is in agreement with previous computational 8 works. [16][17][18] Figure 2: Overhead view of the distribution of hydroxyl groups (light spots) and surface charges (dark spots) in the interfacial layer of the silica substrate used for the atomistic simulations.…”
Section: Computational Approachmentioning
confidence: 99%
“…[16][17][18] This proto- interactions were simulated with Lennard-Jones potentials shifted to smoothly decay to zero at distances larger than 0.9 nm. Electrostatic interactions were calculated by means of the particle mesh Ewald method (PME), 34,35 with a direct space cut-off of 1.3 nm and a Fourier grid spacing of 0.125 nm.…”
Section: Computational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent numerical simulations [14] even suggested that the dichotomy between hydrophobicity and large slip might be purely coincidental and that hydrophilic surfaces can show features typically associated with hydrophobicity. The description of the fluid and surface at atomistic level is essential for these investigations, as small changes in the surface properties can lead to surprisingly different structural and dynamical properties of the fluid, as it is seen for example for hydroxylated surfaces [23,24].…”
Section: Introductionmentioning
confidence: 99%